2014
DOI: 10.1002/cb.1483
|View full text |Cite
|
Sign up to set email alerts
|

Positive outcomes of social norm transgressions

Abstract: Norm transgressions occur when consumers behave outside social expectations; such transgressions often cause embarrassment for the perpetrator and negative responses from witnesses. This study asks if norm violations can lead to positive audience responses. The study relies on 246 written reports from norm breakers and finds positive audience responses occurring almost 17 per cent of the time, with an additional 26 per cent of cases providing a mix of both positive and negative reactions. A content analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Studies conducted in Italy and the United States similarly showed that individuals who entered a boutique wearing gym clothes rather than appropriate attire or who attended a black tie event wearing a red tie were ascribed higher status (Bellezza, Gino, & Keinan, 2014). Moreover, research in marketing and psychology showed that norm violators whose behavior benefited others were more likely to be given a leadership role (Popa, Phillips, & Robertson, 2014; Van Kleef, Homan, Finkenauer, Blaker, & Heerdink, 2012).…”
Section: Reactions To Norm Violationsmentioning
confidence: 99%
“…Studies conducted in Italy and the United States similarly showed that individuals who entered a boutique wearing gym clothes rather than appropriate attire or who attended a black tie event wearing a red tie were ascribed higher status (Bellezza, Gino, & Keinan, 2014). Moreover, research in marketing and psychology showed that norm violators whose behavior benefited others were more likely to be given a leadership role (Popa, Phillips, & Robertson, 2014; Van Kleef, Homan, Finkenauer, Blaker, & Heerdink, 2012).…”
Section: Reactions To Norm Violationsmentioning
confidence: 99%
“…In addition to inspiring perceptions of power, norm violations may fuel power affordance, the process of advancing another person's position in the hierarchy by granting them power. Indeed, recent studies have shown that norm violators get afforded more power as long as the norm violation benefits observers (Popa, Phillips, & Robertson, 2014;van Kleef, Homan, Finkenauer, Blaker, & Heerdink, 2012). For instance, a confederate who stole coffee from the experimenter's desk was afforded more power than a confederate who took coffee upon invitation, but only when he also offered coffee to the participant (van Kleef et al, 2012).…”
Section: Social Norms and Reactions To Norm Violationsmentioning
confidence: 99%
“…Indeed, empirical studies have shown that individuals who violated prevailing norms were considered more powerful than individuals who complied with the norms (Stamkou, Van Kleef, Homan, & Galinsky, 2016;Van Kleef, Homan, Finkenauer, Gündemir, & Stamkou, 2011). Moreover, norm violators whose behavior benefited others were more likely to be given a leadership role (Popa, Phillips, & Robertson, 2014;Van Kleef, Homan, Finkenauer, Blaker, & Heerdink, 2012). Other studies showed that individuals who entered a boutique wearing gym clothes rather than appropriate attire or who attended a black tie event wearing a red tie were ascribed higher status because they were considered autonomous (Bellezza, Gino, & Keinan, 2014).…”
mentioning
confidence: 99%